DHPLC-Based Method for DNA Methylation Analysis of Differential Methylated Regions from Imprinted Genes. (February 2003) - Couvert, P.; Poirier, K.; Carrié, A.; Chalas, C.; Jouannet, P.; Beldjord, C.; Bienvenu, T.; Chelly, J.; Kerjean, A.
The bisulfite genomic sequencing method is one of the most widely used techniques for methylation analysis in heterogeneous unbiased PCR, amplifying for both methylated and unmethylated alleles simultaneously. However, it requires labor-intensive and time-consuming cloning and sequencing steps. In the current study, we used a denaturing high-performance liquid chromatography (DHPLC) procedure in a complementary way with the bisulfite genomic sequencing to analyze the methylation of differentially methylated regions (DMRs) of imprinted genes. We showed reliable and reproducible results in distinguishing overall methylation profiles of DMRs regions of human SNRPN, H19, MEST/PEG1, LIT1, IGF2, TSSC5, WT1 antisense, and mouse H19, Mest/Peg1, Igf2R imprinted genes. These DHPLC profiles were in accordance with bisulfite genomic sequencing data and may serve as a type of "fingerprint, " revealing the overall methylation status of DMRs associated with sample heterogeneity. We conclude that DHPLC analysis could be used to increase the throughput efficiency of methylation pattern analysis of imprinted genes after the bisulfite conversion of genomic DNA and unbiased PCR amplification.